Response of carbon and nitrogen-rich metabolites to nitrogen deficiency in PSARK::IPT tobacco plants - Rubio-Wilhelmi, María del Mar (Plant physiology and biochemistry : PPB, 2012)
Copyright © 2012 Elsevier Masson SAS. All rights reserved.